The Legitimacy of Ondoafi in Conflict Settlement of Customary Land Tenure in Sentani, Papua - Tri Mulyadi; Kamsi Kamsi; Surwandono Surwandono; Trisno Raharjo (Jurnal Media Hukum, 2019)
The charismatic power of ondoafi as a leader in customary government can determine the direction of the policy including the resolution of problems of indigenous people. In the new order Era, ondoafi was not involved further in resolving land issues, so he would not be labeled as part of the Free Papua Movement (OPM). In the Special Autonomy era, the roles of ondoafi got stronger as indicated by the privileges given by the government to indigenous people in Papua. This paper explores the roles of ondoafi in resolving the conflict over the customary land in Sentani, Jayapura, Papua, using a qualitative approach with secondary data. The result of the research shows that ondoafi could not resolve the conflict over the customary land in Sentani effectively due to the discrepancy of values between the conflicting parties. Nevertheless, ondoafi should become a mediator to resolve the conflicts between indigenous people and non-indigenous people; including privates or corporates and the central government. An ondoafi should be able to become a diplomat who can bridge the values differences between the conflicting parties and urge the conflicting parties to understand others’ interests and values so that conflicts can be resolved in a peaceful manner.